Implementasi Supervisi Akademik Kepala Madrasah dalam Meningkatkan Kinerja Guru di MA DA Jerowaru: Implementation of Academic Supervision by Madrasah Principals in Improving Teacher Performance at MA DA Jerowaru - Sukranudin (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2026)
This study aims to analyze and describe the implementation of academic supervision carried out by the madrasah principal in improving teacher performance at MA DA Jerowaru. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that the madrasah principal has implemented academic supervision systematically through the stages of planning, implementation, and follow-up of supervision. Supervision is carried out in the form of class visits, group discussions, and individual coaching, which is focused on improving the quality of the learning process. The implementation of this supervision contributes positively to improving teacher performance, which is reflected in the improvement of pedagogical, professional, and managerial competencies. Despite several obstacles such as limited time and lack of motivation as a teacher, the madrasah principal continues to strive to overcome these obstacles through a persuasive and collaborative approach. Thus, academic supervision carried out by the madrasah principal has proven effective in supporting the improvement of teacher performance at MA DA Jerowaru.